In vivo study of Fagonia Cretica Linn toxicity in Sudan - Abbas, Omer; Izzeldin, Omer; Abdalla, Rashid (International Journal of Pharmacology and Toxicology, 2014)
Purpose: The study targeted to determine the toxicological effects of ethanolic extracts of Fagonia cretica linn plant in Khartoum, Omdurman, and Shendi towns in Sudan during (January – February) 2013. Objectives: To determine the LD50 of the plant and to study the effects of the plant on the body weight, on vital organ weights, and anesthesia induction time effects. Methods: Different methods were adopted to achieve the objectives of this study, including Harborne methods for extraction. A total of (30), young adult Wistar rats, weighing (42.6 – 72.2) grams, fed standard rat food and water d libitum, were maintained at standard laboratory conditions. All rats were grouped into (3) groups, survived through the experiment by using the recommended progression doses of Fagonia cretica as (175, 550, 1750, 5000, 5000, & 5000) mg/kg/body weight screen shot of AOT425 statistical program of main test. Toxicological studies in vivo (LD50 determination) were done in all (3) groups of animals survive till the experiment was over after the administration of a selected high dose (5000) mg/kg/body weight. Ethical approval had been obtained from Omdurman Islamic University, Faculty of Pharmacy, and Department of Pharmacology under the number-(01/0/2013). Results: The LD50 is greater than 5000 mg/kg, indicates the high safety of the plant. The ethanolic extract of Fagonia cretica in doses of (100 & 300 mg/kg/body weight) has no effects on the rats relative vital organ weight (heart, liver, kidneys, lung and spleen) during the study period of (14) days compared to the control group whilst the dose of (600) mg/kg/body weight change the liver somewhat from the relevant control, although, has no effects on the rats body weight during the study period of (14) days compared to the control group monitored at day (0, 7, 14). The anesthesia induction time on rats, shows that the ethanolic extracts of the plant has neurological effect on rats. Conclusion: The toxicological determination of LD50 was found to be greater than (5000) mg/Kg, estimated by the special statistical software with three stopping criteria based on long term outcomes. This is indicating wide safety margin of Fagonia ethanolic extract which encourages its use by humans for the treatment of many diseases.. Keywords: Fagonia Cretica Linn, Umm Showaika, Ethanolic Extraction, Toxicity.